School-to-work and school-to-university transition and health inequalities among young adults: a scoping review - Matos Fialho, Paula Mayara; Dragano, Nico; Reuter, Marvin; Deindl, Christian; Schleberger, Sarah; Metzendorf, M.; Hoffmann, Stephanie; Diehl, Katharina; Wachtler, Benjamin; Schuttig, Wiebke; Herke, Max; Richter, Matthias; et al. (BMJ Open, 2022)
OBJECTIVES: The main objective was to systematically map evidence regarding the emergence of health inequalities in individuals aged 16-24 years during school-to-work and school-to-university transition (STWT). Second, we aimed to summarise the evidence on potential effects of contextual and compositional characteristics of specific institutional contexts entered during STWT on health and health behaviours. DESIGN: Scoping review. STUDY SELECTION: Relevant literature was systematically searched following the methodological framework proposed by Arksey and O'Malley. Ovid MEDLINE and Web of Science, and websites of the International Labour Organization and National Institute for Occupational Safety and Health were searched, using a predetermined search strategy. Articles in English or German published between 1 January 2000 and 3 February 2020 were considered. DATA EXTRACTION: To collect the main information from the selected studies, a data extraction spreadsheet was created. Data were summarised and grouped into five health outcomes and five institutional contexts (school, vocational training, university, work, unemployment). RESULTS: A total of 678 articles were screened for inclusion. To be able to draw a picture of the development of various health outcomes over time, we focused on longitudinal studies. Forty-six prospective studies mapping health-related outcomes during STWT were identified. Higher family socioeconomic position (SEP) was associated with higher levels of health behaviour and lower levels of health-damaging behaviour, but there was also some evidence pointing in the opposite direction. Disadvantaged family SEP negatively impacted on mental health and predicted an adverse weight development. There was limited evidence for the outcomes physical/somatic symptoms and self-rated health. Meso-level characteristics of the institutional contexts identified were not systematically assessed, only individual-level factors resulting from an exposure to these contexts, rendering an analysis of effects of contextual and compositional characteristics on health and health behaviours impossible. CONCLUSIONS: This scoping review demonstrated a wide range of health inequalities during STWT for various health outcomes. However, knowledge on the role of the core institutional contexts regarding the development of health inequalities is limited.
CRIS-Team Scopus Importer:2022-07-22
Keywords: mental health; public health; social medicine